Robustly Inorganic Solar Steam Generator Derived from Hollow Glass Microspheres Based Composites for Desalination. Issue 12 (10th November 2021) - Wang, Shuo; Niu, Ye; Ye, Xingyun; Liu, Fang; Su, Min; Zhu, Zhaoqi; Sun, Hanxue; Li, Jiyan; Liang, Weidong; Li, An
Abstract : Solar steam generation (SSG) offers a clean and sustainable way to produce freshwater from seawater or polluted water by harvesting solar energy. However, it remains a great challenge to integrate all the desired functions in a single evaporation system by using low‐cost materials and simple methods. Herein, we report the design and fabrication of a novel inorganic solar steam evaporator (PPy‐HGMAM) through binding the building block of hollow glass microspheres (HGM) and pore‐forming material of melamine sponge (MS) with interconnection network structure by aluminum dihydrogen phosphate adhesive followed by coating of polypyrrole (PPy) as light absorption layer for efficient SSG. With the merits of high porosity, low thermal conductivity both in the wet (0.107 W m −1  k −1 ) and dry (0.056 W m −1  k −1 ) states, super‐hydrophilicity, and strong light absorption (92%), the as‐prepared porous PPy‐HGMAM shows high energy conversion efficiency (92.9%) and evaporation rate (1.56 kg m −2  h −1 ) under 1 sun (1 kW m −2 ) illumination, as well as excellent salt‐resistance performance. Combined with its high mechanical strength, self‐floating ability, environment‐friendly, and low cost, along with simple and scalable preparation method, our inorganic PPy‐HGMAM evaporator may hold the great potential for practical large‐scale application in SSG. Abstract : Herein, the design and fabrication of a novel inorganic solar steam evaporator (PPy‐HGMAM) based on hollow glass microspheres (HGM) with high mechanical strength, self‐floating ability, environment‐friendly, and low cost, which shows high energy conversion efficiency (92.9%), as well as excellent salt‐resistance performance and can be used for clean water production from seawater or wastewater, are reported.